Decision Support System Skill Consultant PT. Qims Intrasindo uses the SAW method - Vita Monica Sari; Eko Hariyanto (INFOKUM, 2022)
This research requires a method that can solve problems in the search for consultants who have special skills according to consumer needs based on predetermined criteria. This study uses the SAW method in determining the skills of consultants who can solve problems that consumers have in order to be more efficient and more precise. In the decision support system for determining the skills of this consultant, the admin no longer uses manual systems such as using paper or writing in inputting data, but using applications that have been built, so that admins are easier to input . consultant data.